Sortase A: A chemoenzymatic approach for the labeling of cell surfaces. Issue 12 (27th September 2021) - Kumari, Poonam; Bowmik, Sujoy; Paul, Sudipto Kumar; Biswas, Bidisha; Banerjee, Sanjay K.; Murty, Upadhyayula Surayanarayana; Ravichandiran, Velayutham; Mohan, Utpal
Abstract: Sortase A, a transpeptidase enzyme is present in many Gram‐positive bacteria and helps in the recruitment of the cell surface proteins. Over the last two decades, Sortase A has become an attractive tool for performing in vivo and in vitro ligations. Sortase A‐mediated ligation has continuously been used for its specificity, robustness, and highly efficient nature. These properties make it a popular choice among protein engineers as well as researchers from different fields. In this review, we give an overview of Sortase A‐mediated ligation of various molecules on the cell surfaces, which can have diverse applications in interdisciplinary fields. Abstract : Systemic representation of enzyme‐based labeling for cell surface modifications. Enzymes recognize specific substrate sequence and assist in the ligating molecules onto the cell surface